2013
DOI: 10.1177/0731684413509701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of macromolecular silane coupling agent on the mechanical properties of nano-SiO2/cyanate ester nanocomposites

Abstract: In this paper, a novel kind of high-performance composite was developed by blending 2, 2′-Bis(4-cyanatophenyl)isopropylidene with nano-silica (nano-SiO2), in which the nano-SiO2 was modified by a tri-copolymer of styrene, vinyltrimethoxysilane and methacrylate. The transmission electron microscopic and scanning electron microscopic micrographs indicated that the modified nano-SiO2 particles were dispersed in the 2′-Bis(4-cyanatophenyl)isopropylidene matrix homogeneously. Compared with pure 2′-Bis(4-cyanatophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Although this type of interface is often reported for polycyanurate/silica nanocomposites, other types of surface chemistry may provide significant benefits. For instance, Yan et al 29 recently reported significant improvements in cyanate ester nanocomposite mechanical performance when nanosilicas were modified with resin-compatible terpolymers. Devaraju et al 30 reported the beneficial effects of epoxy group functionalization on the dielectric properties of silicareinforced cyanate ester nanocomposites, while Jothibasu et al 31 examined nanocomposites in which 3-aminopropylsilane was used as a coupling agent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although this type of interface is often reported for polycyanurate/silica nanocomposites, other types of surface chemistry may provide significant benefits. For instance, Yan et al 29 recently reported significant improvements in cyanate ester nanocomposite mechanical performance when nanosilicas were modified with resin-compatible terpolymers. Devaraju et al 30 reported the beneficial effects of epoxy group functionalization on the dielectric properties of silicareinforced cyanate ester nanocomposites, while Jothibasu et al 31 examined nanocomposites in which 3-aminopropylsilane was used as a coupling agent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…So aligned gra modication is needed to improve its dispersion properties. [20][21][22][23] In order to promote the dispersion of POSS particles and ensure the dielectric properties of the material, the mesoporous silica (MPS) 24,25 is used to prepare the modied material. Hui Pan et al prepared a series of silica nanoparticles surface-modied with MPS, which exhibited excellent dispersibility in various solvents or polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, two of the greatest challenges in producing organic-inorganic nanocomposites are the better dispersion of inorganic nanofillers and the stronger interface interactions between inorganic nanofillers and polymer matrix. [3][4][5] Spherical nano-silica (SiO 2 ) as a kind of attractive traditional nanofiller is widely applied to reinforce polymer matrix. The unmodified SiO 2 can disperse well in polymer matrix at very low concentration when the hydrogen-bonding interaction between nano-silica and polymer exists.…”
Section: Introductionmentioning
confidence: 99%